ENTRE OS BRECHÓS E A INTERNET: CIDADANIAS FLUIDAS E IDENTIDADES MEDIADAS POR PRÁTICAS CULTURAIS PRESENCIAIS E VIRTUAIS DOS MODS DE CURITIBA – PARANÁ - Pereira, Daniele Prates (2008)
The present research studies the cultural group of Mods from Curitiba, its name comes from England and means Modernism/Modism. We bring to discussion some cultural practices related to the identification processes of the Mods in Brazil, with a specific scene in Paraná state, visually and organized mainly in Curitiba. Our therical and methodolgical references was based on debates about post-modernity and the specificities of dynamic fluid and intercultural identities in the contemporary world, giving emphasis to the importance of cultural practices and apropriations as ways of expression, socialization and positions related to senses of belonging to groups. Senses and meanings that involve the constructions of speeches about the group itself and the way to see the daily reality and the relations with other cultural groups dialogues with the tension in virtual and presencial spaces of comunitary coexistance. Ideas of identitie, comunity, subjetivity, daily estetization, become keys to understand how these individuals develop their links with ideas and practices of cultural citizenship that happen related to consumption actions. In this research, the consumption acts are defined as a main aspect of the individuals’ actions to Express their identity and Mark their difference to the others. Our analysis shows dilemas, contradictions and ambiguities during the identification processes and cultural practices of the Mods from Curitiba. Mainly when they act in the virtual and presencial scenes, where the mediation of Technologies and products transform and pluralize the sense of belonging. Fluid cultural citizenship are created in these processes, due to contemporary practices that at the same time firm fixed identities and comunities and negotiate the fluidity, plasticity and fragility that are permanent in ways of expression and human relations in the game. So far, the Curitiba Mods, expressing themselves and getting along with other groups transform the meanings of those actions, mainly the consumption and cultural sociability ones, redefining – in a permanent way and even contradictory way – their practices and the border between individuals and groups.